1993
DOI: 10.1128/jb.175.7.1971-1980.1993
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation of ammonia monooxygenase from Nitrosomonas europaea by copper

Abstract: The effect of copper on the in vivo and in vitro activity of ammonia monooxygenase (AMO) from the nitrifying bacterium Nitrosomonas europaea was investigated. The addition of CuCl2 to cell extracts resulted in 5-to 15-fold stimulation of ammonia-dependent 02 consumption, ammonia-dependent nitrite production, and hydrazine-dependent ethane oxidation. AMO activity was further stimulated in vitro by the presence of stabilizing agents, including serum albumins, spermine, or MgCl2. In contrast, the addition of CuCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 59 publications
(58 reference statements)
5
105
0
Order By: Relevance
“…N. europaea (ATCC 19178) was cultured as described, with minor modifications (Ensign et al, 1993;Stein & Arp, 1998). The standard (Fe-replete) medium contained 10 mM Fe 3+ (FeCl 3 ) complexed with EDTA to prevent Fe from precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…N. europaea (ATCC 19178) was cultured as described, with minor modifications (Ensign et al, 1993;Stein & Arp, 1998). The standard (Fe-replete) medium contained 10 mM Fe 3+ (FeCl 3 ) complexed with EDTA to prevent Fe from precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrification of NH 3 to NO − 2 occurs in two steps (7,8). The first step is catalyzed by NH 3 monooxygenase, which uses copper (Cu) and dioxygen (O 2 ) to hydroxylate NH 3 to hydroxylamine (NH 2 OH) (9). In AOB, the second step is thought to be the four-electron oxidation of NH 2 OH to NO − 2 by NH 2 OH oxidoreductase (HAO).…”
mentioning
confidence: 99%
“…Therefore, it is assumed that their key enzyme, the ammonia monooxygenase (AMO), is highly conserved. However, little is known about the structure and function of AMO since the enzyme has not been purified [14,44,45]. Inactivation experiments suggested that the proteins AmoA and AmoB were possible subunits of AMO [33].…”
Section: Discussionmentioning
confidence: 99%